Clitoria ternatea Flower Extract-Based Gel Elevates TGF-β1 Gene Expression and Collagen Density in UVB-Induced Collagen Loss Rat Skin - Christine Magdalena Hutapea; Prasetyowati Subchan; Agung Putra (Fakultas Kedokteran Universitas Brawijaya, 2023)
Ultraviolet B (UVB) irradiation on the skin induces collagen loss by the ROS pathways and pro-collagen factors, mainly the TGF-β family. Many studies of antioxidant compounds in Clitoria ternatea have shown to induce decreasing ROS production, in the collagen loss process. However, the molecular mechanism of action is still not clearly studied, inducing the mechanism of TGF-β1 activation and regulation of collagen loss need to be explored. This study aimed to investigate the effect of Clitoria ternatea flower extract-based gel on TGF-β1 gene expression and collagen density in UVB-induced rat skin. A randomized control group post-test-only design was conducted on 20 male Wistar rats aged 8-10 weeks (150-250 grams). Rats were divided into four groups: Untreated group (Healthy Control), UVB+Based gel group (Negative Control), 5% Clitoria ternatea flower extract-based gel group (T-5%), and 10% Clitoria ternatea flower extract-based gel group (T-10%). Rats exposed to UVB for 5 consecutive days and treated with gel every day for two weeks. At week 3, rat skins were isolated for TGF-β1 gene expression using qRT-PCR, and Masson Trichrome-collagen specific staining. Comparative analysis of qRT-PCR showed that the lowest mean TGF-β1 expression was seen in the Negative Control group (0.01±0.00), followed by T-5% (0.11±0.22), Healthy Control group (1.01±0.01) and T-10% (2.32±2.46). The highest amount of collagen is in the Healthy Control group (43.83±5.3), followed by T-10% (38.39±3.1), T-5% (29.04±3.2), and the Negative Control group. (13.87±2.7). Clitoria ternatea flower extract-based gel may increase TGF-β1 gene expression and collagen deposition in the UVB-induced collagen loss rat skin.